Chosen aspects of obstetric care of HIV-infected pregnant women - Filanowicz, Małgorzata; Szynkiewicz, Ewa; Cegła, Bernadeta; Dowbór-Dzwonka, Aneta; Klafta, Małgorzata; Gierszewska, Małgorzata; Pankiewicz, Piotr (Nursing Problems / Problemy Pielęgniarstwa, 2013)
For over a dozen years, constant research and observations have enabled gaining great knowledge about HIV virus, its epidemiology, nosogenesis and treatment. At present, HIV infection is considered to be a chronic illness whose course can be slowed down by giving appropriate medicine. A cooperation between the medical staff and a patient is necessary for the therapy to be effective. In contrast with many other diseases, HIV does not only involve medical aspect, but also a psychological one. The increasing number of women infected with HIV/AIDS means the rise of infected pregnant women as well as the growth of risk of vertical infection. In the same time, when the knowledge about the HIV is still growing, a standard of the care for people living with HIV, also of pregnant women and their offspring is changing. The aim of this work is taking a closer look at the importance of nursing care of a HIV-infected pregnant woman. The main goal of care should be an efficient therapy. Antiretrovirus treatment protects the infected against opportunist ilnesses and prolongs life, and sometimes enables the patient to lead a similar lifestyle to the one he or she has led before the infection. Constant education and the appropriate, comprehensive care of people with positive HIV- has the task of providing them with good quality lives. The midwife should be a help in achieving the optimal state of health and the prevention of illnesses. Getting a proper diagnosis and creating the process of looking after the patient are a priority in this profession.